C. F. Lehmann-Haupt`S Studies On Assyrian Inscriptions Of The Armenian Highland - Sargsyan, Vahe («Քոփի Փրինթ» տպ.)
Prominent German orientalist C. F. Lehmann-Haupt explored the Tigris Tunnel during his travels in the Armenian Highland and Northern Mesopotamia from 1898 to 1899.1 According to him, the kings of Assyria considered this place as the source of the Tigris (or at least one of its sources) and tried to reach it during their campaigns. This was probably conditioned by the circumstance that the waters of the Tigris River, which “flooded the walls” of the Assyrian capitals of Assur, Calah and Nineveh, flowed through the rocks there. According to the inscriptions of the Tigris Tunnel, the sacrifices made by the Assyrian kings in honor of their gods were considered to be dedicated to the god of the river and the spring [9: A.0.102.6 ii 34-40; A.0.102.8: 20-23; A.0.102.14: 67-72; 14: 434]. Գերմանացի ականավոր արևելագետ, ուրարտագետ Կ.Ֆ. Լեման-Հաուպտը 1898–1899 թթ. Հայկական լեռնաշխարհում և Հյուսիսային Միջագետքում կատարած իր ճանապարհորդության ժամանակ հետազոտեց նաև Տիգրիսի թունելը: Ըստ հետազոտողի՝ Ասորեստանի արքաներն այդ վայրը համարել են որպես Տիգրիսի ակունքը, կամ՝ ակունքներից մեկը և իրենց արշավանքների ժամանակ ձգտել են հասնել այնտեղ: Դա հավանաբար պայմանավորված էր նաև այն հանգամանքով, որ Ասորեստանի մայրաքաղաքներ Աշշուրի, Կալախի և Նինվեի «պատերը ողողող» Տիգրիս գետի ջրերը, այստեղ հոսում էին ժայռերի միջից: Զոհաբերությունները որոնք, ասորեստանյան արքաներն, ըստ արձանագրությունների, կատարում էին իրենց աստվածների պատվին, համարվել են նաև նվիրված գետի և աղբյուրի աստծուն:
Keywords: Armenian highland